Play to Resolve: Educational Games as a Pathway to Conflict Resolution for Early Learners - Asmara, Berda; Rulyansah, Afib (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores the role of educational games in developing conflict resolution skills among children aged 6 to 8, a critical period for social and emotional development. Utilizing a qualitative research design and an exploratory case study approach, the research was conducted in two educational institutions in X, Indonesia, involving 60 children from diverse socioeconomic backgrounds. This diversity provided insights into how educational games affect children with varying levels of social experience and resource access. Data collection methods included observations, semi-structured interviews, and document analysis. Findings indicate that educational games significantly enhance conflict resolution skills by improving communication, empathy, teamwork, and self-regulation. Children demonstrated increased impulse control and thoughtful responses during game-related conflicts, as reported by teachers and parents. These improvements align with Vygotsky's theory of social development, highlighting the importance of structured play in cognitive and social growth. The study concludes that educational games offer a dynamic platform for practicing conflict resolution, thereby fostering children's social and emotional development. Recommendations for educators include integrating a variety of cooperative and role-playing games into curricula and conducting regular debriefing sessions to reinforce learning. This research underscores the broad applicability of educational games in diverse contexts, supporting their integration into educational settings to equip children with essential life skills.